Effect of a Physical Exercise Program on the Inflammatory Response, Cardiac Functions, Functional Capacity, and Quality of Life in Patients with Sickle Cell Disease - Antonelli Rossi, Daniele Andreza [UNESP]; De Araujo Junior, Jonas Alves [UNESP]; Luvizutto, Gustavo José; Bazan, Rodrigo [UNESP]; Salmazo, Péricles Sidnei; Modolo, Gabriel Pinheiro [UNESP]; Hueb, João Carlos [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Hokama, Newton Key [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Roscani, Meliza Goi; Zanati Bazan, Silméia Garcia [UNESP] (MDPI, 2023)
Introduction: The beneficial effects of physical exercise on functional capacity and inflammatory response are well-known in cardiovascular diseases; however, studies on sickle cell disease (SCD) are limited. It was hypothesized that physical exercise may exert a favorable effect on the inflammatory response of SCD patients, contributing to an improved quality of life. This study aimed to evaluate the effect of a regular physical exercise program on the anti-inflammatory responses in SCD patients. Methods: A non-randomized clinical trial was conducted in adult SCD patients. The patients were divided into two groups: 1—Exercise Group, which received a physical exercise program three times a week for 8 weeks, and; 2—Control Group, with routine physical activities. All patients underwent the following procedures initially and after eight weeks of protocol: clinical evaluation, physical evaluation, laboratory evaluation, quality of life evaluation, and echocardiographic evaluation. Statistical analysis: Comparisons between groups were made using Student’s t-test, Mann–Whitney test, chi-square test, or Fisher’s exact test. Spearman’s correlation coefficient was calculated. The significance level was set at p < 0.05. Results: There was no significant difference in inflammatory response between the Control and Exercise Groups. The Exercise Group showed an improvement in peak VO2 values (p < 0.001), an increase in the distance walked (p < 0.001), an improvement in the limitation domain due to the physical aspects of the 36-Item Short Form Health Survey (SF-36) quality of life questionnaire (p = 0.022), and an increase in physical activity related to leisure (p < 0.001) and walking (p = 0.024) in the International Physical Activity Questionnaire (IPAQ). There was a negative correlation between IL-6 values and distance walked on the treadmill (correlation coefficient −0.444, p = 0.020) and the estimated peak VO2 values (correlation coefficient −0.480; p = 0.013) in SCD patients in both groups. Conclusions: The aerobic exercise program did not change the inflammatory response profile of SCD patients, nor did it show unfavorable effects on the parameters evaluated, and patients with lower functional capacity were those with the highest levels of IL-6.
Keywords: functional capacity; hemoglobinopathies; inflammation; physical activity